Fault detection and diagnosis using Multivariate Statistical Process Control (MSPC) - Mak, Weng Yee; Kamarul, Asri Ibrahim (Penerbit Universiti Sains Malaysia, 2004)
Currently, chemical plants face numerous challenges like stringent requirements are needed on the desired final product quality, utilization of a lot of energy, must be environmentally friendly and fulfill safety requirements. High operation cost is needed in order for chemical plants to overcome the stated challenges. Any faults that are present in a chemical process will yield higher operation cost on the plant due to increase in production of waste, re-work, re-processing and consumption of utilities. Therefore, accurate process fault detection and diagnosis (FDD) on a chemical process at an early stage is important to reduce the cost of operation due to present of faults.